2018
DOI: 10.3389/fmicb.2018.01794
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation in Cereals

Abstract: Cereals such as maize, rice, wheat and sorghum are the most important crops for human nutrition. Like other plants, cereals associate with diverse bacteria (including nitrogen-fixing bacteria called diazotrophs) and fungi. As large amounts of chemical fertilizers are used in cereals, it has always been desirable to promote biological nitrogen fixation in such crops. The quest for nitrogen fixation in cereals started long ago with the isolation of nitrogen-fixing bacteria from different plants. The sources of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(144 citation statements)
references
References 161 publications
(193 reference statements)
0
128
0
2
Order By: Relevance
“…The present study shows that the beneficial endophytes E. cloacae RCA25 and H. huttiense RCA24 can be promising strains to improve, directly or indirectly, nitrogen fixation in rice plants under greenhouse conditions. Challenging projects are trying to genetically modify cereals to enhance diazotrophs colonization or to engineer bacterial competitiveness and ammonium release (Geddes et al ., ; Fox et al ., ; Rosenblueth et al ., ). The data here reported highlight that the assessment of location and distribution of the individual microbial components within the plant tissues is fundamental for the selection of bio‐inoculants, able to enhance nitrogen‐fixing ability of the host plants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study shows that the beneficial endophytes E. cloacae RCA25 and H. huttiense RCA24 can be promising strains to improve, directly or indirectly, nitrogen fixation in rice plants under greenhouse conditions. Challenging projects are trying to genetically modify cereals to enhance diazotrophs colonization or to engineer bacterial competitiveness and ammonium release (Geddes et al ., ; Fox et al ., ; Rosenblueth et al ., ). The data here reported highlight that the assessment of location and distribution of the individual microbial components within the plant tissues is fundamental for the selection of bio‐inoculants, able to enhance nitrogen‐fixing ability of the host plants.…”
Section: Discussionmentioning
confidence: 97%
“…The internal plant tissues constitute a favourable environment for N-fixation performed by diazotrophic endophytes: the competition with other microbes in the rhizosphere is minimized and a microaerobic environment, necessary for nitrogenase activity, is provided (Mus et al, 2016;Kandel et al, 2017). In the last few years, a wide diversity of bacteria associated with cereals have shown to possess the nifH gene coding for dinitrogenase reductase (Rosenblueth et al, 2018). This gene is considered the most genetically conserved within the nif regulon and traditionally used as a marker gene to study the genetic diversity of diazotrophs in nature (Gaby and Buckley, 2014;Gaby et al, 2018;Angel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying suitable combinations of candidate genes from the symbiotic pathway is a continual process and relevant efforts are in progress to enhance nitrogen fixation through a transgenic approach [126]. With the advancements in transcriptomics and proteomics, data modelling and targeted selection, the search for candidate symbiotic genes has been efficiently bypassed.…”
Section: Application Of Transgenic Approaches and Genome Editingmentioning
confidence: 99%
“…Symbiotic bacteria associate with plants forming root nodules (rhizobia), where they fix nitrogen while benefiting from plant photoassimilates. It has been observed that this symbiosis occurs not only in plants from the Leguminosae family [71] but also in cereals such as rice, maize, and wheat from the Poaceae family [73]. BNF also occurs in nonsymbiotic associations.…”
Section: Biological Nitrogen Fixationmentioning
confidence: 99%
“…BNF also occurs in nonsymbiotic associations. Endophytic bacteria colonize plant tissues and fix N while benefiting from plant photoassimilates, although the amount of N fixed is lower than in symbiosis [73,74]. Also, free-living microorganisms inhabiting rhizosphere, soil region around plant roots, fix nitrogen while feeding on root exudates (amino acids, peptides, proteins, enzymes, vitamins, and hormones), which stimulate growth of diazotrophic bacteria from genera Acetobacter, Azoarcus, Azospirillum, Azotobacter, Beijerinckia, Burkholderia, Enterobacter, Herbaspirillum, Klebsiella, Paenibacillus, and Pseudomonas [71].…”
Section: Biological Nitrogen Fixationmentioning
confidence: 99%